Capsaicin Inhibits Shigella flexneri Intracellular Growth by Inducing Autophagy - Basak, Priyanka; Maitra, Priyanka; Khan, Uzma; Saha, Kalyani; Bhattacharya, Satya Sundar; Dutta, Moumita; Bhattacharya, Sushmita (Frontiers in Pharmacology, 2022)
Antibiotic treatment plays an essential role in preventing Shigella infection. However, incidences of global rise in antibiotic resistance create a major challenge to treat bacterial infection. In this context, there is an urgent need for newer approaches to reduce S flexneri burden. This study largely focuses on the role of a herbal compound capsaicin (Caps) in inhibiting S flexneri growth and evaluating the molecular mechanism behind bacterial clearance. Here, we show for the first time that Caps inhibits intracellular S flexneri growth by inducing autophagy. Activation of autophagy by Caps is mediated through transcription factor TFEB, a master regulator of autophagosome biogenesis. Caps induced nuclear localisation of TFEB. Activation of TFEB further induces gene transcription of autophagosomal genes. Our findings revealed that inhibition of autophagy by silencing TFEB and Atg5 induces bacterial growth. Hence, Caps induced autophagy is one of the key factors responsible for bacterial clearance. Moreover, Caps restricted the intracellular proliferation of S flexneri resistant strain. The efficacy of Caps in reducing S flexneri growth is confirmed in animal model. This study showed for the first time that S flexneri infection can be intervened by inducing autophagy. Overall observations suggest that Caps activates TFEB to induce autophagy and thereby combat S flexneri infection.